2018
DOI: 10.1016/j.molcel.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

mHTT Seeding Activity: A Marker of Disease Progression and Neurotoxicity in Models of Huntington’s Disease

Abstract: Self-propagating, amyloidogenic mutant huntingtin (mHTT) aggregates may drive progression of Huntington's disease (HD). Here, we report the development of a FRET-based mHTT aggregate seeding (FRASE) assay that enables the quantification of mHTT seeding activity (HSA) in complex biosamples from HD patients and disease models. Application of the FRASE assay revealed HSA in brain homogenates of presymptomatic HD transgenic and knockin mice and its progressive increase with phenotypic changes, suggesting that HSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 66 publications
2
68
0
2
Order By: Relevance
“…2F). We previously reported that Htt ex1 Q25-YFP aggregates formed in the glial cytoplasm co-localized with a similarly smaller-sized subpopulation of Htt ex1 Q91-mCherry aggregates from DA1 ORN axons (Pearce et al, 2015), and smaller mHtt ex1 aggregates are associated with increased seeding-propensity and neurotoxicity in other HD models (Ast et al, 2018; Chen et al, 2001). Taken together, these findings strongly suggest that Htt ex1 Q91-mCherry aggregates formed in presynaptic ORNs gain access to the cytoplasm of postsynaptic PNs to effect prion-like conversion of Htt ex1 Q25-GFP, and that Htt ex1 Q91-mCherry aggregate transmissibility is inversely correlated with aggregate size.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2F). We previously reported that Htt ex1 Q25-YFP aggregates formed in the glial cytoplasm co-localized with a similarly smaller-sized subpopulation of Htt ex1 Q91-mCherry aggregates from DA1 ORN axons (Pearce et al, 2015), and smaller mHtt ex1 aggregates are associated with increased seeding-propensity and neurotoxicity in other HD models (Ast et al, 2018; Chen et al, 2001). Taken together, these findings strongly suggest that Htt ex1 Q91-mCherry aggregates formed in presynaptic ORNs gain access to the cytoplasm of postsynaptic PNs to effect prion-like conversion of Htt ex1 Q25-GFP, and that Htt ex1 Q91-mCherry aggregate transmissibility is inversely correlated with aggregate size.…”
Section: Resultsmentioning
confidence: 98%
“…Draper could also selectively deplete a subpopulation of larger neuronal aggregates from which smaller transmissible species are produced. Interestingly, seeding propensity is correlated with smaller mHtt ex1 aggregate size in other HD models (Ast et al, 2018; Chen et al, 2001), and secondary nucleation processes initiated by aggregate fragmentation are thought to drive amplification of prion-like particles in many neurodegenerative diseases (Knowles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from full‐length mHTT, truncated N‐terminal polyQ‐containing fragments may also play a critical role in HD (Davies et al ; Ast et al ). The mHTTex1 fragment has been reported to efficiently self‐assemble into higher order structures such as spherical oligomers or amyloid fibrils in vitro and in vivo (Sathasivam et al ; Sahoo et al ; Wagner et al ).…”
Section: Various Putatively Pathogenic Mhtt Protein Species Have Beenmentioning
confidence: 99%
“…Recent studies from different laboratories demonstrated that polyQ‐expanded mHTTex1 fibrils, rather than oligomers or misfolded monomers exert toxicity in HD (Drombosky et al ). Minute amounts of small self‐propagating HTTex1Q97 fibrils in neurons were shown to be sufficient to dramatically shorten the life‐span of HD transgenic flies (Ast et al ). Here, it is important to note that misfolded mHTTex1 monomers and oligomers are structurally distinct from amyloid fibrils.…”
Section: Various Putatively Pathogenic Mhtt Protein Species Have Beenmentioning
confidence: 99%